2019
DOI: 10.1017/s0033291719003271
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between autistic traits, insufficient sleep, and real-world executive functions in children: a mediation analysis of a national epidemiological survey

Abstract: Background Although the literature documents low executive functions and sleep deficits in individuals with autism spectrum disorder or subclinical autistic traits, no study has simultaneously examined their relationships in the general child population. This study aimed to examine whether autistic traits impacted real-world executive functions through insufficient sleep in a nationally representative sample of children. Methods This was a national survey of 6832 primary and secondary sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…While no SRS subscales were signi cantly associated with sleep at baseline, all SRS subscales except motivation was associated with sleep across timepoints. Our nding of a signi cant effect of sleep on BRIEF global composite is supported by a previous study reporting sleep de cits were associated with a worse global composite score on the BRIEF [9]. Contrary to expectations, the effect of sleep on BRIEF subscales did not reach signi cance at baseline.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…While no SRS subscales were signi cantly associated with sleep at baseline, all SRS subscales except motivation was associated with sleep across timepoints. Our nding of a signi cant effect of sleep on BRIEF global composite is supported by a previous study reporting sleep de cits were associated with a worse global composite score on the BRIEF [9]. Contrary to expectations, the effect of sleep on BRIEF subscales did not reach signi cance at baseline.…”
Section: Discussionsupporting
confidence: 76%
“…In cross-sectional studies, sleep mediates the relationships between restrictive and repetitive behaviors and real-world executive function, [9] while in a study of boys with ASD, sleep disturbance was found to moderate the relationship between ASD symptom severity and problem behaviors [10]. Moreover, clinical trials of effective sleep interventions in children with neurodevelopmental disorders improved a range of behavioral and mood symptoms for at least six months post-treatment [11][12][13].…”
Section: Trial Registrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Items are rated as 1 (never), 2 (sometimes), and 3 (often). The BRIEF in Chinese has been used in epidemiological (Tsai, Chen, & Gau, 2019) and clinical (Goto et al 2017) research.…”
Section: Behavioral Measures (See Supplementary Methods)mentioning
confidence: 99%